The Relationship of Spiritual Intelligence and Rehabilitation Staff's Perceived Stress in Welfare Organizations Centers in Tehran and Shemiranat: 2017 - Banafsheh Ebrahimi Barmi; Mohammadali Hosseini; Kianoush Abdi; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Today, one of the factors that threatens the mental health of the employees is the stress of their organizations. The nature and essence of the medical organizations are such that these environments inevitably impose stress on employees. Perceived stress at work affects the quality and performance of an employee. Knowing how to cope with perceived stress can be effective in preventing and reducing complications. The rehabilitation work environments are in high stress and this stress can exacerbate the quality of the work of experts and ultimately affect the health of staff. This study aimed to determine the relation of spiritual intelligence with rehabilitation staff's perceived stress in welfare organization centers in Tehran City and Shemiran County, Iran in 2017. Materials & Methods This research is a correlational and cross-sectional study. A total of 163 rehabilitation experts (in different fields of physiotherapy, occupational therapy, speech therapy, audiology, optometry, technical orthopedics, and psychology) worked in welfare organization centers of Tehran City and Shemiran County were selected by random cluster sampling method in 2017. In order to collect data, a demographic questionnaire, Spiritual Intelligence Questionnaire (2008) (Cronbach α=0.88) and perceived stress Cohen (1983) (Cronbach α=0.84) were used. The validity and reliability of the tools used in this research have been approved by other researchers in similar studies. To analyze the data, SPSS version 21 was used. Descriptive statistics such as mean and standard deviation were used to describe the data. Regarding the normal distribution of data, Pearson correlation coefficient was used to analyze the data. The Independent t test was used to compare the two groups data. Results The average age of the study participants was 40 years, ranged from 23 to 54 years. About 56.5% of the participants in this study were female and 22.9% had a work experience of 10-15 years. The results showed no relationship between age, sex, work experience, marital status, education and type of employment with spiritual intelligence and perceived stress. However, there was a significant correlation between spiritual intelligence and perceived stress (P=0.042). Conclusion According to the findings, people with high perceived stress, have low spiritual intelligence. In order to boost spiritual intelligence and reduce the perceived stress of individuals, it is recommended that spiritual intelligence be taught to employees at regular intervals. Since the researcher has used the questionnaire as the only measurement tool in collecting data, it is necessary to be cautious in interpreting the results. Therefore, for more comprehensive research, techniques such as viewing, interviewing, and analyzing content are recommended.